The politics of desire Foucault, Deleuze, and psychoanalysis - Colombo, Agustín; McGushin, Edward F.; Pfeifer, Geoff (Rowman & Littlefield, 2022)
"This book will gather contributions from international scholars with the aim of exploring the political reflection of Deleuze-Guattari's and Foucault's critical encounter with psychoanalytic thought: their possible connections, their divergences and the fields of reflection that this encounter opens, the problems and debates that lead Foucault and Deleuze to engage with psychoanalysis"--